Replicative and stress-induced premature senescence distinctively affect the endothelial anticoagulation capacity - Akiko Katayama; Koji Ikeda; Tomoya Kitani; Ekura Yamazaki; Daisuke Ueno; Fumiaki Ito; Satoaki Matoba (PLoS ONE, 2026)
Aging is strongly associated with an increased risk of morbidity and mortality from multiple diseases, including thromboembolic disorders. Endothelial dysfunction is considered a key contributor to age-related thrombus formation, although its underlying mechanisms remain incompletely understood. Cellular senescence is a fundamental driver of aging; however, the distinct functional roles of replicative (RS) and stress-induced premature senescence (SIPS) in cellular functions remain unclear. This study, investigated the effects of endothelial cell (EC) senescence on blood coagulation, and demonstrated that RS and SIPS differentially regulate endothelial anticoagulation capacity. Plasma coagulation capacity, assessed using calibrated automated thrombogram, was unexpectedly reduced in the presence of RS-ECs compared with that in the presence of young control cells, whereas SIPS-EC showed no such effect. RNA sequencing analysis revealed distinct global transcriptional and coagulation pathway-related alterations between RS- and SIPS-ECs. Despite enhanced anticoagulation capacity in RS-ECs in vitro , thrombus formation was exacerbated in naturally aged mice in vivo . The contribution of SIPS-ECs to thrombus formation was further evaluated in vivo using EC-specific SIPS mouse models. EC-specific SIPS mice exhibited aggravated venous thrombus formation, with thrombus histological features resembling those observed in naturally aged mice. Gene expression profiles related to blood coagulation were also largely similar between ECs isolated from naturally aged and EC-specific SIPS mice. These findings demonstrate distinct contributions of endothelial RS and SIPS to blood coagulation and suggest that SIPS, rather than RS, may represent the predominant form of endothelial senescence during in vivo aging with respect to age-related dysregulation of blood coagulation.